2010
DOI: 10.1152/jn.00438.2010
|View full text |Cite
|
Sign up to set email alerts
|

Postsynaptic Cell Type–Dependent Cholinergic Regulation of GABAergic Synaptic Transmission in Rat Insular Cortex

Abstract: Yamamoto K, Koyanagi Y, Koshikawa N, Kobayashi M. Postsynaptic cell type-dependent cholinergic regulation of GABAergic synaptic transmission in rat insular cortex. J Neurophysiol 104: 1933-1945. First published August 4, 2010 doi:10.1152/jn.00438.2010. The cerebral cortex consists of multiple neuron subtypes whose electrophysiological properties exhibit diverse modulation patterns in response to neurotransmitters, including noradrenaline and acetylcholine (ACh). We performed multiple whole cell patch-clamp re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 48 publications
1
34
0
Order By: Relevance
“…suggested that this effect, together with the muscarinic and nicotinic increase in excitability of the layer V PCs resulted in the generation of Ca 2+ spikes and bursts of action potentials (APs) of the PCs when inputs in basal dendrites were stimulated [71]. Heterogeneous effects at FS cell terminals on INs, as well as on the terminals of non-identified ‘non FS cells’ on PCs were reported [91•,93]. …”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…suggested that this effect, together with the muscarinic and nicotinic increase in excitability of the layer V PCs resulted in the generation of Ca 2+ spikes and bursts of action potentials (APs) of the PCs when inputs in basal dendrites were stimulated [71]. Heterogeneous effects at FS cell terminals on INs, as well as on the terminals of non-identified ‘non FS cells’ on PCs were reported [91•,93]. …”
Section: Figurementioning
confidence: 99%
“… h Pronounced inhibition of GABA release at the presynaptic basket terminals of PV-expressing FS INs on PCs has been observed in somatosensory and insular cortices [91•,93], and Nunez et al . suggested that this effect, together with the muscarinic and nicotinic increase in excitability of the layer V PCs resulted in the generation of Ca 2+ spikes and bursts of action potentials (APs) of the PCs when inputs in basal dendrites were stimulated [71].…”
Section: Figurementioning
confidence: 99%
“…Evidence from GC recordings showing that ACh can decrease a cell's best response to a tastant while increasing its non-best responses to other tastants is consistent with such a rearrangement of taste coding [28] in response to behavioral state. This modulation could involve rearrangements of the balance between excitation and inhibition by cholinergic inputs: ACh reduces inhibitory transmission onto pyramidal cells and had mixed effects on connections between inhibitory interneurons in GC [29]. The final results of these changes would be a shift away from sparse taste representations (typically observed in anesthetized states) to dense, population-based, representations characteristic of wakefulness.…”
Section: Introductionmentioning
confidence: 99%
“…All data were collected for the RMT analysis and have not been published elsewhere. The imbalance of the sample size between HFB and non-HFB neurons was caused by their population in the IC, as shown in our previous in vitro study (Yamamoto et al, 2010). Based on this study, we performed the following statistical tests without any correction.…”
Section: Methodsmentioning
confidence: 78%